Rozwój manufaktur żelaznych w drugiej połowie XVIII w. oraz proces przemian w górnictwie i hutnictwie do czasów Księstwa Warszawskiego na przykładzie Zakładów Klucza Samsonowskiego w Zagłębiu Staropolskim - Czmuchowski, Adam (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2006)
In the middle of the 18lh century, there were very important course changes in a range of production relations. The article presents this problem on the example of changes in Samsonow factories town in the Old-Polish Industrial Zone - its extension in the second half of the 18lh century and then its being passed on from the Cracow Bishopric to the Treasury, to which it belongs till formation of the Warsaw Princedom. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Nauki Humanistyczne (10); 2006; nr 1149, s. 86-108